"Man, I shop like a woman!" The effects of gender and emotions on consumer shopping behaviour outcomes. Issue 9 (2nd September 2014) - Maurer Herter, Márcia; Pizzutti dos Santos, Cristiane; Costa Pinto, Diego
Abstract : Purpose: – Research suggests that women demonstrate higher levels of shopping satisfaction, recommendation, return intentions, and hedonic shopping than men. However, is it possible to reduce the effects of gender on shopping behaviour? The purpose of this paper is to explore how the interaction between gender and emotions affects consumers' shopping behaviour outcomes. Design/methodology/approach: – Two studies show the effects of gender and emotions on shopping behaviour outcomes. Study 1 is a field experiment that tests the effects of gender and emotions (positive vs neutral) on consumer satisfaction, recommendation, and return intentions. Study 2 is a laboratory experiment that explores the effects of gender and emotions (positive, neutral, and negative) on hedonic shopping. Findings: – Results demonstrate that positive (vs neutral) emotions increase shopping behaviour outcomes for men, to reach the same level as for women. The findings also indicate that retail environment perception mediates the effects. Moreover, the results show that positive emotions increase levels of hedonic shopping for men and that negative emotions reduce levels of hedonic shopping for women. Practical implications: – This paper helps retailers enhance shopping behaviour outcomes in retail environments. From a managerial perspective, the findings also provide insights on how to improve shopping behaviour outcomes for male consumers. Originality/value: – This paper shows how to reduce gender effects on consumer shopping behaviour outcomes by activating specific emotions in retail environments. This research also demonstrates the mediating role of retail environment perception.